ONLINE LEARNING MEDIA FOR FOREIGN LANGUAGE CLASSROOM - Lina Septianasari; Dinar Romadina (JELLi Journal, 2019)
The use of online learning media is not a new thing in English Foreign Language (EFL) classrooms. This research aimed to investigate the use of online learning media for online learning activities. The participants of this research were some teachers and students from several senior high schools in the Bogor area. This is a type of qualitative research with a descriptive approach where observation and documentation were conveyed to collect the data. The results showed that WhatsApp is the most favourable media to be utilized in teaching and learning activities. It eases the teachers to communicate with the students on an online basis.